The effect of chloroquine phosphate on C-reactive protein and erythrocyte sedimentation rate measurement in knee osteoarthritic patients. - Eman S. S. (College of Pharmacy / Mustansiriyah University, 2011)
Osteoarthritis (OA) is the most common articular disease world wide. It is the result of both mechanical and biological events that destabilize the normal coupling of degeneration synthesis of articular cartilage and subchondral bone. Rheumatologist often routinely order tests for rheumatoid factor and erythrocyte sedimentation rate (ESR) for all patients with joint complaints as well as C - reactive protein (CRP) as a laboratory marker important in the assessment of inflammation. Anti malarial drugs are used for treatment of many rheumatic diseases. Chloroquine phosphate (CQP) was used previously as a disease modifying anti rheumatic drug and in this study its effect appears through decreasing the measurement of erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) in knee osteoarthritic patients (KOA). Abbreviation: HCQ, hydroxy chloroquine; CQ, chloroquine; DMARD, disease modifying anti rheumatic drug; APP, acute phase protein; ACR, American College of Rheumatology; RA, rheumatoid arthritis; SLE, systemic lupus erythematosus; RF, rheumatoid factor.